Peran Guru Pendidikan Agama Islam Dalam Menanamkan Nilai-Nilai Karakter Islami Peserta Didik Di SMA Islam Duduksampeyan Gresik - Urifah, Afifatul; Siti Suwaibatul Aslamiyah (Pendidikan Agama Islam, 2025)
This study examines “The Role of Islamic Religious Education Teachers in Instilling Islamic Character Values in Students at SMA Islam Duduksampeyan Gresik.” It employs a qualitative research type with a descriptive approach. The purpose of this study is to understand the role of Islamic religious education teachers in instilling Islamic character values in students at SMA Islam Duduksampeyan Gresik and to identify the supporting and inhibiting factors affecting the role of these teachers in instilling Islamic character values in students. The results of this study indicate that the role of Islamic religious education teachers consists of three aspects: the role of the teacher as an instructor, which involves teaching material to students; the role of the teacher as an educator, which involves nurturing the morals, behavior, and character of students; and the role of the teacher as a trainer, which involves instilling discipline and religious habits in students. Additionally, the supporting factors include school regulations, routine religious activities, and adequate facilities and infrastructure. The inhibiting factors include the influence of social media, peer environment, and lack of self-awareness.